ENGAGEMENT OF STUDENTS IN ONLINE LEARNING PLATFORMS: FOLLOW-UP STUDY IN LITHUANIAN GENERAL EDUCATION SCHOOLS - Batuchina, Aleksandra; Melnikova, Julija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Online learning platforms with integrated tools of learning analytics (LA) and artificial intelligence (AI) are growing in popularity in general education in Lithuania. Such platforms have a number of advantages in terms of the teaching-learning process, however, there is a lack of research about such aspects of use platforms in general education schools. The follow-up study was organized in schools that participated in the DIMA project for three months and tested different platforms with learning analytics and artificial intelligence components - LearnLab and Eduten Playground. The study aimed to monitor children's progress with the platform, tracking interest and engagement. The same questionnaire was given 3 times within the period of one month. In total, 977 responses were received: 404 students completed in first time; 281 completed second and 252 completed 3d time. Results have showed that the students feel positive about working with online learning platforms, moreover every single time are becoming more engaged in the learning process, since they get acquainted navigation and operation of the program. As a result, the engagement of the students into online learning platforms depends not only on the quality or other features of online learning platforms, but also the ability of students to navigate within the program.